"Investigating the Diagnostic Overshadowing Bias in Bangladeshi Health Professionals". Issue 1 (2nd January 2021) - Hinde, Kylie; Mason, Jonathan; Kannis-Dymand, Lee; Millear, Prudence; Sultana, Razia
ABSTRACT: Introduction : Intellectual disability (ID) and co-morbid mental health problems are more common in developing countries such as Bangladesh. However, little is known about how Bangladeshi health practitioners diagnose mental health disorders in people with an ID. Studies in developed countries have explored the impact of the diagnostic overshadowing bias (DOB): the tendency for health practitioners to misattribute mental health symptomology to a client's ID, rather than a separate mental health disorder. To date, no study has investigated the presence of the DOB in Bangladesh. Method : A range of Bangladeshi health practitioners ( N = 243) were randomly assigned a clinical vignette describing a client displaying symptoms of a mental health disorder. Vignette 1 described a client with an IQ of 105 who graduated from secondary school. Vignette 2 described a client with an IQ of 55 who attended special education. All other details were identical. Participants rated the likelihood of seven mental health diagnoses on a 5-point Likert scale. Results : Practitioners were more likely to diagnose schizophrenia, drug problems and being bullied in people with a typical IQ compared to those with an ID. Doctors, psychiatrists, and psychologists appeared to be more affected by the DOB than community health workers, traditional healers, and allied health practitioners. Conclusion : Findings indicate that the bias may be present in Bangladesh healthcare professionals. The development and implementation of specific training programs to meet the differing needs of practitioners, across the health fields are recommended.